A unique deoxyguanosine triphosphatase is responsible for the optA1 phenotype of Escherichia coli. - Beauchamp, B B (1988)
Escherichia coli optA1, a mutant unable to support the growth of T7 phage containing mutations in gene 1.2, contains reduced amounts of dGTP. Extracts of E. coli optA1 catalyze the hydrolysis of dGTP at a rate 50-fold greater than do extracts of E. coli optA+. The dGTPase responsible for the increased hydrolysis has been purified to apparent homogeneity. Purification of the protein is facilitated by its high affinity for single-stranded DNA. By using this purification scheme an identical dGTPase has been purified from E. coli optA+. The purified proteins catalyze the hydrolysis of dGTP to yield deoxyguanosine and tripolyphosphate. The products of hydrolysis, chromatographic properties, denatured molecular mass of 56 kDa, N-terminal amino acid sequence, substrate specificity, and heat inactivation indicate that the proteins purified from optA1 and from optA+ cells are identical and identify the enzyme as the deoxyguanosine 5'-triphosphate triphosphohydrolase purified to homogeneity from wild-type E. coli [Seto, D., Bhatnagar, S. K. & Bessman, M. J. (1988) J. Biol. Chem. 263, 1494-1499]. OptA1 cells contain approximately equal to 50-fold more active molecules of the 56-kDa dGTPase than do E. coli optA+ cells.